2021
DOI: 10.1021/acs.jafc.1c04195
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Odorants in Chardonnay Marc Skins

Abstract: Chardonnay marc, consisting of grape skins, seeds, and stems, is a coproduct of grape juice production for Chardonnay wine making. The discovery that marc contains a rich source of health-promoting molecules has led to its growing popularity as a flavorful healthy food ingredient. However, the odorants responsible for its pleasant fruity aroma remain unknown. In this study, 35 odorants were identified in Chardonnay marc skins using solvent-assisted flavor evaporation (SAFE) and aroma extract dilution analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…They were then ground and put into 20 mL scintillation vials where trained panelists were asked to compare the intensity of attributes in each of the components (Table ). These attributes were determined by free choice profiling in a previous study determining the odorants in Chardonnay skins . In the current Chardonnay seed study, the panelists agreed that the descriptors from the previous study embodied the aroma of the seed component of the marc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were then ground and put into 20 mL scintillation vials where trained panelists were asked to compare the intensity of attributes in each of the components (Table ). These attributes were determined by free choice profiling in a previous study determining the odorants in Chardonnay skins . In the current Chardonnay seed study, the panelists agreed that the descriptors from the previous study embodied the aroma of the seed component of the marc.…”
Section: Resultsmentioning
confidence: 99%
“…Several odorants were identified in the seed sample with an FD factor of 64 including hexanal ( 5 , green), linalool ( 20 , floral-citrus), 3-methylnonane-2,4-dione ( 25 , hay), ( 2E , 4E )-nona-2,4-dienal ( 24 , fatty), and 2-phenylethanol ( 32 , floral-rose) (Figure ). All five of the odorants identified in the seed sample with an FD factor of 64 were also previously identified in Chardonnay skins and occurred in the skin sample with an OAV ≥ 1 . The odorants with an FD factor of 16 included ( Z )-4-heptenal ( 8 , fatty), 3-(methylsulfanyl)propanal ( 17 , potato), (2 E )-non-2-enal ( 19 , green), (2 E ,4 Z )-deca-2,4-dienal ( 26 , fatty), HDMF ( 36 , caramel), and δ-nonalactone ( 38 , coconut).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, this collection of odorants was determined to play an important role in the pleasant aroma quality of Chardonnay marc skins. 155 In another recent study applied to the seed component of Chardonnay marc, forty-three odorants were identified including six with flavor dilution (FD) factors ≥64. The odorant with the highest FD factor was (2E,4E)-deca-2,4dienal (fatty) with an FD factor of 1024.…”
Section: ■ Deciphering the Flavor Chemistry Of Chardonnay Marc: An Ep...mentioning
confidence: 99%
“…An odor simulation model prepared using reference odorants with OAVs > 1 was a close match sensorially to the aroma of the Chardonnay marc skins. Accordingly, this collection of odorants was determined to play an important role in the pleasant aroma quality of Chardonnay marc skins . In another recent study applied to the seed component of Chardonnay marc, forty-three odorants were identified including six with flavor dilution (FD) factors ≥64.…”
Section: Deciphering the Flavor Chemistry Of Chardonnay Marc: An Epic...mentioning
confidence: 99%
See 1 more Smart Citation